2021
DOI: 10.1111/jocn.15675
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare professionals' views of a new second‐level nursing associate role: A qualitative study exploring early implementation in an acute setting

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 26 publications
2
30
0
Order By: Relevance
“…Similarly, Lucas et al, ( 2021a ) found that second level nurses have been plagued by both role ambiguity, and intra‐ and inter‐professional conflict over the years. NA stakeholders in particular report a lack of a clear NA job descriptions and a requirement to jump between roles (Lucas et al, 2021b ). Furthermore, King et al, ( 2020a ) found that TNAs themselves were unsure of the scope of their role, adding to the confusion experienced by wider healthcare teams.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, Lucas et al, ( 2021a ) found that second level nurses have been plagued by both role ambiguity, and intra‐ and inter‐professional conflict over the years. NA stakeholders in particular report a lack of a clear NA job descriptions and a requirement to jump between roles (Lucas et al, 2021b ). Furthermore, King et al, ( 2020a ) found that TNAs themselves were unsure of the scope of their role, adding to the confusion experienced by wider healthcare teams.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, some participants faced barriers to progression, including uncertainty about embarking on further intensive training, a factor also reflected in previous research (Kessler et al, 2020c ). Some felt that employers were withholding development opportunities to fit with their preferred service model, and this is reflected in previous cases where employers have insisted on NAs staying in their role for a period prior to undertaking RN training (Lucas et al, 2021b ; Kessler et al, 2020b ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our choice of thematic analysis as opposed to another qualitative analysis method was guided by other studies that have used theoretical frameworks to aid in data collection, in combination with thematic analysis to identify common themes pertaining to the research questions and theoretical frameworks [ 10 , 25 27 , 29 31 ]. Such an approach was appropriate as the purpose of this study was to investigate specific aspects of the participants use of ANDA feedback and desired changes to the feedback provided, to inform the development of interventions in the subsequent trial.…”
Section: Methodsmentioning
confidence: 99%